Oil removal filter material as well as preparation method and application thereof

By using the foam glass oil removal filter made by the sintering foaming method, the strong magnetic properties of NdFeB are used to destroy the stable interface of the emulsified oil, solving the problem of poor emulsification and oil removal in the prior art, achieving efficient oil-water separation, and having the characteristics of low cost and environmental protection.

CN119793072AActive Publication Date: 2025-04-11BEIJING ZHONGKE KANGLUN ENERGY TECH CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202510150848.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-11
Publication Date
2025-04-11
Estimated Expiration
2045-02-11

AI Technical Summary

Technical Problem

The prior art has poor demulsification and oil removal effect when treating oil-containing wastewater, and traditional filter materials are prone to cause plate bonding, affecting treatment efficiency.

Method used

Use waste glass particles and neodymium iron boron waste particles as raw materials, and the foaming method is used to make foam glass oil removal filter material through the presence of foaming agent, foaming accelerator and silane coupling agent. The strong magnetic properties of neodymium iron boron are used to destroy the stable interface of the emulsified oil and achieve oil-water separation.

Benefits of technology

The oil removal filter has excellent emulsion and oil removal ability, improves the quality of the effluent, and is not prone to clogging. The backwash can be completed with a low flow rate of clean water, which is cheap and economical and environmentally friendly.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119793072A_ABST
    Figure CN119793072A_ABST
Patent Text Reader

Abstract

The embodiment of the invention discloses an oil removal filter material as well as a preparation method and application thereof. The preparation method of the oil removal filter material comprises the following steps: by taking waste glass particles and neodymium iron boron waste particles as raw materials, in the presence of a foaming agent, a foaming accelerant and a silane coupling agent, drying, sintering and foaming, naturally cooling to normal temperature, and crushing to obtain the oil removal filter material. The oil removal filter material provided by the invention has better demulsification and oil removal effects, improves the effluent quality, is not easy to block, can complete backwashing by using clear water with the flow rate of 10-20 BV / h, takes waste glass and neodymium iron boron waste as raw materials, has the characteristics of low cost, economy and environmental protection, conforms to the concept of energy conservation and environmental protection in the current society, and has wide application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The embodiments of the present invention relate to the field of water treatment technology, and specifically to an oil removal filter material and a preparation method and application thereof. Background Art

[0002] Oily wastewater mainly comes from petrochemical, coal chemical, mechanical processing, textile industry, etc., and its oil is highly emulsified and difficult to biodegrade. Semi-coke wastewater is mainly produced in the wet quenching unit of semi-coke cooling and the residual circulating ammonia unit of coal gas purification. The semi-coke wastewater pretreatment section is affected by the blockage of emulsified oil, which seriously affects the effluent water quality and project progress. Effective pretreatment and emulsified oil removal technology is the key to realizing the resource utilization and efficient treatment of semi-coke wastewater.

[0003] The particle size of emulsified oil is 0.1-10μm, which can form a relatively stable dispersion state with water. The oil-water interface of emulsified oil is the reason for the stable existence of emulsified oil, and destroying the oil-water interface film is the key to oil removal. The traditional pretreatment process uses quartz sand as filter material, which has a small specific surface area and low porosity. The hydroxyl groups on the surface of quartz sand are distributed disorderly, coupled with each other, and have low activity. The filter material is severely compacted during use.

[0004] Seyyedali Mirshahghassemi et al. synthesized magnetic Fe3O4 nanoparticles coated with PVP for adsorption and removal of oil in wastewater. A high-gradient magnetic separator composed of two NdFeB magnets was used to separate the Fe3O4 nanoparticles after adsorption of oil, and the oil removal rate in wastewater was as high as 95%. However, the operation is rather cumbersome. First, the magnetic Fe3O4 needs to be added to the water sample and stirred for about 1 hour, and then the water sample is extracted using a peristaltic pump. The water sample passes through the magnetic separator, so that the magnetic Fe3O4 in the water sample is adsorbed on the steel wool in the middle of the magnetic separator. The biggest disadvantage is that the steel wool needs to be removed and cleaned, and cleaning is also difficult.

[0005] Patent CN 104998466 B proposes a lightweight filter medium foam glass for water treatment. By increasing the specific surface area and porosity of the glass filter material, it can effectively filter and intercept suspended matter during water treatment and has a good turbidity removal effect. However, when treating oily wastewater, its demulsification and oil removal effect is poor. Summary of the invention

[0006] To this end, the embodiment of the present invention provides an oil removal filter material and a preparation method and application thereof. The oil removal filter material has a better demulsification and oil removal effect, improves the water quality of the effluent, and is not prone to clogging. Backwashing can be completed using a clean water flow rate of 10-20BV / h. At the same time, waste glass and NdFeB waste are used as raw materials, and it has the characteristics of low cost, economy and environmental protection. It conforms to the concept of energy conservation and environmental protection in today's society and has broad application prospects.

[0007] In order to achieve the above purpose, the embodiment of the present invention provides the following technical solutions:

[0008] According to the first aspect of an embodiment of the present invention, the present invention provides a method for preparing an oil-removing filter material, which uses waste glass particles and NdFeB waste particles as raw materials, and after drying, sintering and foaming are carried out in the presence of a foaming agent, a foaming promoter and a silane coupling agent, and then cooled to room temperature and crushed to obtain the oil-removing filter material.

[0009] Most of the oil droplets in oil-in-water (O / W) oily wastewater are negatively charged and can be adsorbed by positively charged magnetic particles. The oil removal filter material of the present invention uses inorganic broken glass as a carrier and NdFeB permanent magnets as core materials. NdFeB permanent magnets have high magnetism and a large attraction between them and oil droplets, which promotes the magnetic particles to destroy the stable interface of emulsified oil in the water phase, so that the oil droplets can be demulsified and agglomerated on the magnetic particles, thus achieving oil-water separation.

[0010] Furthermore, by weight, the waste glass particles are 30-70 parts, the NdFeB waste particles are 5-15 parts, the foaming agent is 0.5-13 parts, the foaming promoter is 1-10 parts, and the silane coupling agent is 1-10 parts.

[0011] Furthermore, the foaming agent is selected from one or more of carbon black, silicon carbide, calcium carbonate, dolomite, phlogopite, graphite, and manganese dioxide.

[0012] Furthermore, the foaming promoter is selected from one or more of sodium nitrate, soda ash, sodium fluorosilicate, sodium carbonate, and ethylenediamine salt.

[0013] Furthermore, the silane coupling agent is selected from one or more of vinyl silane, amino silane, and methacryloxy silane.

[0014] Furthermore, the drying conditions are: temperature 150-200°C, time 1-3h;

[0015] The sintering and foaming conditions are: keeping the temperature at 500-620°C for 30-60min, then increasing the temperature to 1000-1500°C at 20-30°C / min for foaming, the foaming time is 0.5-2h, and then keeping the temperature at 1050-1110°C for 3-5h.

[0016] The particle size of the oil removal filter material is 30-60 mm.

[0017] Furthermore, the preparation method of the waste glass particles is: the waste glass is acid-washed and alkali-washed in sequence, and then crushed to obtain waste glass particles with a particle size of 1-10 mm;

[0018] The pickling process comprises: placing the waste glass in 1-3 mol / L hydrochloric acid, soaking for 1-3 hours at 20-40° C., and washing with water;

[0019] The alkaline washing process comprises: placing the acid-washed waste glass in alkaline soap water with a concentration of 0.2%-0.5%, soaking at 20-40° C. for 1-3 hours, washing with water, and drying at 105-110° C. for 2-3 hours.

[0020] Waste glass is an inorganic non-metallic material, containing SiO2, sodium silicate, calcium silicate, etc. The main component is silicate complex salt, which is an amorphous solid with irregular structure. After acid washing and alkali washing, the inorganic salts, minerals, metal debris, fat and protein on the surface of the waste glass can be cleaned, which is beneficial to the subsequent operation of the product and the controllability of the final product.

[0021] Furthermore, the preparation method of the NdFeB waste particles is as follows: the NdFeB waste is acid-washed and alkali-washed in sequence, and then crushed to obtain NdFeB waste particles with a particle size of 1-10 mm;

[0022] The pickling process comprises: placing the NdFeB waste in 0.5-2 mol / L hydrochloric acid, soaking it at 20-40° C. for 1-2 hours, and washing it with water;

[0023] The alkaline washing process comprises: placing the acid-washed NdFeB waste in 1-3 mol / L sodium hydroxide, soaking at 60-70° C. for 1-3 hours, washing with water, and drying at 105-110° C. for 2-3 hours.

[0024] NdFeB scrap (permanent magnet) is rich in rare earth elements such as Nd, Pr, Dy, etc., with a rare earth element content of about 30% (of which neodymium accounts for about 90%, and the rest are praseodymium, gadolinium, terbium, dysprosium, holmium, etc.), iron content of about 65%, boron content of about 1%, and a small amount of trace elements such as aluminum and copper. After acid washing and alkali washing, the NdFeB scrap can be cleaned of metal debris, surface oxides, fat and protein on the surface of the NdFeB scrap, which is conducive to the subsequent operation of the product and the controllability of the final product.

[0025] According to a second aspect of an embodiment of the present invention, the present invention provides an oil removal filter material, which is made by any of the methods described above.

[0026] According to a third aspect of an embodiment of the present invention, the present invention provides use of the oil removal filter material as described above in removing emulsified oil from a water body.

[0027] The embodiments of the present invention have the following advantages:

[0028] The oil removal filter material of the present invention is made of waste glass, NdFeB waste, foaming agent, foaming promoter and silane coupling agent as raw materials, and is made into foam glass oil removal filter material through low temperature sintering-high temperature foaming method. It has the properties of strong magnetism, high porosity, large specific surface area, light weight, etc. It has excellent adsorption and demulsification ability for oil, so that oil droplets are rapidly aggregated. During use, the filtration speed is fast, the oil removal effect is good, and the expansion rate of the filter material during backwashing is about 50%, which is conducive to fast and effective backwashing. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] In order to more clearly illustrate the implementation methods of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for the implementation methods or the description of the prior art. Obviously, the drawings in the following description are only exemplary, and for ordinary technicians in this field, other implementation drawings can be derived from the provided drawings without creative work.

[0030] Figure 1 This is a scanning electron microscope image of the oil removal filter material of Example 1 of the present invention. DETAILED DESCRIPTION

[0031] The following is a description of the implementation of the present invention by specific embodiments. People familiar with the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0032] In the following content, the method for preparing waste glass particles comprises the following steps:

[0033] (1) Acid washing: Put waste glass (mainly scraps from glass product manufacturers and household garbage) into a 2 mol / L hydrochloric acid cleaning tank for washing. After soaking for 1 hour, take out the glass and wash it with a high-pressure water gun to remove impurities such as hydrochloric acid on the glass surface;

[0034] (2) Alkaline washing: the glass washed in step (1) is soaked in 0.5% alkaline soap water for 1 hour, the glass is taken out and rinsed with a high-pressure water gun until no foam is generated, and the washed glass is dried at 105° C. for 2 hours;

[0035] (3) Crushing: The dried glass in step (2) is crushed to obtain waste glass particles with a particle size of 1-10 mm, which are stored for later use.

[0036] The method for preparing NdFeB waste particles comprises the following steps:

[0037] (1) Pickling: Place the NdFeB waste (mainly scraps from the production process) in a 2 mol / L hydrochloric acid cleaning tank, rinse the NdFeB waste, soak for 1 hour, and then remove the coating on the surface of the waste;

[0038] (2) Alkali washing: the waste material after acid washing in step (1) is placed in a 65°C hot alkali tank (2 mol / L sodium hydroxide) and soaked for 2 h, rinsed with a high-pressure water gun, and the washed NdFeB waste material is dried at 105°C for 2 h;

[0039] (3) crushing; crushing the NdFeB waste dried in step (2) to obtain NdFeB waste particles with a particle size of 1-10 mm, and sealing and storing them to prevent the magnetism from being weakened by long-term contact with moisture and oxygen in the air.

[0040] Example 1

[0041] This embodiment provides an oil removal filter material, and the preparation method thereof is as follows:

[0042] Take 30 parts of waste glass particles, 8 parts of NdFeB waste particles, 1 part of a composite foaming agent composed of manganese dioxide, SiC, and Si3N4 in a mass ratio of 2:4:4, 1 part of sodium nitrate, and 2 parts of vinyl silane. Mix the above materials evenly, spread the obtained mixed powder evenly in a square mold (ceramic fiber paper), dry at 150°C for 1 hour, and then directly put it into a muffle furnace that has been pre-heated to a sintering temperature of 550°C for sintering. The sintering time is 30 minutes, and then rise to 1100°C at 20°C / min for foaming. The foaming time is 0.5h. After completion, keep warm at 1050°C for 3h, finally cool naturally to room temperature, and crush to obtain an oil removal filter material with a particle size of 30-40mm.

[0043] Example 2

[0044] This embodiment provides an oil removal filter material, and the preparation method thereof is as follows:

[0045] Take 30 parts of waste glass particles, 5 parts of NdFeB waste particles, 2 parts of a composite foaming agent composed of CaCO3 and SiC in a mass ratio of 1:1, 2 parts of soda ash, and 1 part of aminosilane, mix the above materials evenly, spread the obtained mixed powder evenly in a square mold (ceramic fiber paper), dry at 200℃ for 2h, and then directly put it into a muffle furnace that has been pre-heated to a sintering temperature of 580℃ for sintering. The sintering time is 30min, and then rise to 1300℃ at 25℃ / min for foaming. The foaming time is 1h. After completion, keep it at 1050℃ for 5h, finally cool it naturally to room temperature, and crush it to obtain an oil removal filter material with a particle size of 50-60mm.

[0046] Example 3

[0047] This embodiment provides an oil removal filter material, and the preparation method thereof is as follows:

[0048] Take 50 parts of waste glass particles, 8 parts of NdFeB waste particles, 5 parts of a composite foaming agent composed of phlogopite and graphite in a mass ratio of 7:3, 2 parts of ethylenediamine salt, and 1 part of methacryloyloxysilane, mix the above materials evenly, spread the obtained mixed powder evenly in a square mold (ceramic fiber paper), dry at 180℃ for 3h, and then directly put it into a muffle furnace that has been pre-heated to a sintering temperature of 600℃ for sintering. The sintering time is 60min, and then rise to 1500℃ at 30℃ / min for foaming. The foaming time is 1h. After completion, keep it at 1110℃ for 5h, finally cool it naturally to room temperature, and crush it to obtain an oil removal filter material with a particle size of 40-50mm.

[0049] Comparative Example 1

[0050] This comparative example provides an oil removal filter material, and its preparation method is as follows:

[0051] Take 30 parts of waste glass particles, 1 part of a composite foaming agent composed of manganese dioxide, SiC, and Si3N4 in a mass ratio of 2:4:4, 1 part of sodium nitrate, and 2 parts of vinyl silane. Mix the above materials evenly, spread the obtained mixed powder evenly in a homemade square mold (ceramic fiber paper), dry at 150°C for 1h, and then directly put it into a muffle furnace that has been pre-heated to a sintering temperature of 550°C for sintering. The sintering time is 30min, and then rise to 1100°C at 20°C / min for foaming. The foaming time is 0.5h. After completion, keep warm at 1050°C for 3h, finally cool naturally to room temperature, and crush to obtain a glass filter material with a particle size of 30-40mm.

[0052] Test Example 1

[0053] The oil removal filter material of Example 1 was subjected to a scanning electron microscope test, and the electron microscope image is shown in Figure 1 The electron microscope image shows obvious bumps and texture features, reflecting that the glass filter material has a large specific surface area, is light in weight, and has many bright parts, proving that the filter material is uniform.

[0054] The oil removal filter materials of Examples 1-3 were subjected to performance tests, and the results are shown in Table 1 below.

[0055] Table 1

[0056]

[0057]

[0058] Test Example 2

[0059] The oil removal filter materials of Examples 1-3 and Comparative Example 1 and a commercially available glass filter material were loaded into columns separately, and the feed liquid before pretreatment of blue coke from a certain factory (the feed liquid contained a large amount of phenolic substances and emulsified oil) was input at a flow rate of 5 BV / h using a bottom-in and top-out method. The effluent was collected and allowed to stand for 2 hours to separate into layers. The lower layer of feed liquid was taken for analysis of the oil content. The results are shown in Table 2 below.

[0060] Table 2 The first round of comparative oil removal test data

[0061]

[0062] After the above adsorption column runs for 1500 BV, it is backwashed with clean water, the flow rate is set to 15 BV / h, and the backwashing is 30 minutes. After backwashing, the second round of pretreatment oil removal experiment is carried out. The backwashing and second round of pretreatment data are shown in Table 3-4.

[0063] Table 3 Backwashing experimental data

[0064]

[0065]

[0066] Table 4 Second round of comparative oil removal test data

[0067]

[0068] The results show that the oil removal filter material provided by the embodiment of the present invention can significantly reduce the oil content when conducting pretreatment oil removal experiments on oily wastewater, significantly improve the treated water quality, and can operate smoothly and for a long time. In addition, it has high backwashing efficiency and can be used repeatedly.

[0069] Although the present invention has been described in detail above by general description and specific embodiments, it is obvious to those skilled in the art that some modifications or improvements can be made to the present invention. Therefore, these modifications or improvements made without departing from the spirit of the present invention all belong to the scope of protection claimed by the present invention.

Claims

1. A method for preparing an oil removal filter material, characterized in that: The waste glass particles and NdFeB waste particles are used as raw materials, in the presence of a foaming agent, a foaming accelerator and a silane coupling agent, after drying, sintering and foaming, cooling to room temperature, and crushing to obtain the oil removal filter material.

2. The method for preparing the oil removal filter material according to claim 1, characterized in that: In terms of weight, the waste glass particles are 30-70 parts, the NdFeB waste particles are 5-15 parts, the foaming agent is 0.5-13 parts, the foaming promoter is 1-10 parts, and the silane coupling agent is 1-10 parts.

3. The method for preparing the oil removal filter material according to claim 1, characterized in that: The foaming agent is selected from one or more of carbon black, silicon carbide, calcium carbonate, dolomite, phlogopite, graphite and manganese dioxide.

4. The method for preparing the oil removal filter material according to claim 1, characterized in that: The foaming promoter is selected from one or more of sodium nitrate, soda ash, sodium fluorosilicate, sodium carbonate, and ethylenediamine salt.

5. The method for preparing the oil removal filter material according to claim 1, characterized in that: The silane coupling agent is selected from one or more of vinyl silane, amino silane and methacryloxy silane.

6. The method for preparing the oil removal filter material according to claim 1, characterized in that: The drying conditions are: temperature 150-200°C, time 1-3h; The sintering and foaming conditions are: sintering at a temperature of 500-620°C for 30-60min, then increasing the temperature to 1000-1500°C at 20-30°C / min for foaming, the foaming time is 0.5-2h, and after completion, keeping the temperature at 1050-1110°C for 3-5h; The particle size of the oil removal filter material is 30-60 mm.

7. The method for preparing the oil removal filter material according to claim 1, characterized in that: The method for preparing the waste glass particles comprises: washing the waste glass with acid and washing with alkali in sequence, and then crushing the waste glass to obtain waste glass particles with a particle size of 1-10 mm; The pickling process comprises: placing the waste glass in 1-3 mol / L hydrochloric acid, soaking for 1-3 hours at 20-40° C., and washing with water; The alkaline washing process comprises: placing the acid-washed waste glass in alkaline soap water with a concentration of 0.2%-0.5%, soaking at 20-40° C. for 1-3 hours, washing with water, and drying at 105-110° C. for 2-3 hours.

8. The method for preparing the oil removal filter material according to claim 1, characterized in that: The method for preparing the NdFeB waste particles is as follows: the NdFeB waste is sequentially acid-washed and alkali-washed, and then crushed to obtain NdFeB waste particles with a particle size of 1-10 mm; The pickling process comprises: placing the NdFeB waste in 0.5-2 mol / L hydrochloric acid, soaking it at 20-40° C. for 1-2 hours, and washing it with water; The alkaline washing process comprises: placing the acid-washed NdFeB waste in 1-3 mol / L sodium hydroxide, soaking at 60-70° C. for 1-3 hours, washing with water, and drying at 105-110° C. for 2-3 hours.

9. An oil removal filter material, characterized in that: It is made by the method according to any one of claims 1-8.

10. Use of the oil removal filter material according to claim 9 in removing emulsified oil from water.

Citation Information

Patent Citations

  • A lightweight filter medium for water treatment, its preparation method and application

    CN104998466B

  • Preparation method and application of magnetic demulsifier capable of simultaneously achieving efficient oil-water separation of O / W and W / O emulsions

    CN110613960A

  • Hydrophobic glass filter material, and preparation method and application thereof

    CN113735462A

  • Silver-doped surface modified multifunctional filter material as well as preparation method and application thereof

    CN116059739A

  • Synthetically manufactured foam glass and filter device

    EP1900698A1